2017
DOI: 10.1016/j.crvi.2017.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Developing eco-friendly biofungicide for the management of major seed borne diseases of rice and assessing their physical stability and storage life

Abstract: Three plant oils (Cymbopogon citratus, Cymbopogon martini, and Pelargonium graveolens) were developed as EC formulations and tested for their physical stabilities. EC formulations (10EC, 20EC and 30EC) of C. citratus, C. martini and P. graveolens had emulsion stability, spontaneity property, heat and cold stability. EC formulated plant oils were screened against the major seed borne fungi of rice such as Curvularia lunata, Fusarium moniliforme, Bipolaris oryzae, and Sarocladium oryzae. The level of inhibition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 23 publications
0
12
0
1
Order By: Relevance
“…Here, the seed treatment with 0.5 mg/mL C. citratus essential oil significantly increased the plantlet emergence, reduced the incidence of seedborne S. cucurbitacearum for the various parts of the plantlets, without any significant differences compared to the fungicides. Naveenkumar et al [54] reported that for Oryza sativa (rice) seedlings, a C. citratus essential oil increased the seed germination, shoot length, root length, and vigor. Also, a C. citratus essential oil was shown to reduce the severity of S. cucurbitacearum infections in melon plants [34].…”
Section: Discussionmentioning
confidence: 99%
“…Here, the seed treatment with 0.5 mg/mL C. citratus essential oil significantly increased the plantlet emergence, reduced the incidence of seedborne S. cucurbitacearum for the various parts of the plantlets, without any significant differences compared to the fungicides. Naveenkumar et al [54] reported that for Oryza sativa (rice) seedlings, a C. citratus essential oil increased the seed germination, shoot length, root length, and vigor. Also, a C. citratus essential oil was shown to reduce the severity of S. cucurbitacearum infections in melon plants [34].…”
Section: Discussionmentioning
confidence: 99%
“…Se ha reportado en Bangladés (Naher et al, 2016), Chad (Signaboubo et al, 2016), Cuba (Duarte et al, 2014), Egipto (Ibrahim et al, 2014, India (Naveenkumar et al, 2017), Irán (Monajjem et al, 2014), México (Hernández-Arenas et al, 2012), Nepal (Pandey et al, 2020), Nigeria (Yusuf et al, 2018), Pakistán (Aurangzeb et al, 2014) y Tanzania (Kwaloe et al, 2018). Este hongo ocasiona el bakanae del arroz, pudrición de raíz y corona, ahogamiento, etiolación, atrofia, hipertrofia, panículas con granos vanos, esterilidad y granos manchados (Bashyal, 2018;Franco et al, 2018).…”
Section: Curvularia Lunata (Wakker) Boedijnunclassified
“…But one of the major constrains in rice production is diseases caused by bacteria, fungi, viruses and nematodes; and are responsible for major economic losses in India (Mew and Gonzales, 2003). As such rice, is known to be affected by as many as a total of 153 seedborne pathogens among which 18% are of quarantine importance, 65% are native pathogen and 17% are storage pathogens (Naveenkumar, 2017) in India. Agrawal (1999) reported more than 50 fungal pathogens to be seed-borne in rice.…”
Section: Introductionmentioning
confidence: 99%